Unique Trans-fatty Acid Profile in Children With Attention Deficit Hyperactivity Disorder - Armon-Omer, Ayelet; Amir, Eti; Neuman, Hadar; Khateeb, Saleh; Mizrachi, Itai; Shalan, Monia; Tamir, Snait; Yatzkar, Uri (Frontiers in Psychiatry, 2021)
Background: Attention deficit hyperactivity disorder (ADHD) is the most common developmental disorder in children. Studies suggest an association between fatty acids composition and ADHD pathogenesis. We aimed to investigate whether children diagnosed with ADHD present unique fatty acid profiles in red blood cells (RBC), as compared to children without ADHD. Method: We examined 60 children aged 6-14 years, out of which 32 were diagnosed with ADHD, and 28 were not. Blood was collected from all children to quantify an array of 26 fatty acids from RBC membranes. Fatty acid methyl esters were generated by acid transesterification and analyzed by gas chromatography. Results: We found that children with ADHD presented unique fatty acid profiles on RBC membranes with significantly higher levels of most of the trans-fatty acids (Total trans-fatty acids 0.64±0.21 vs. 0.49±0.18 p=0.003) and lower levels of docosahexaenoic acid (DHA), as compared to controls (4.06±0.79 vs. 4.68±1.37 p=0.040). Additionally, total trans-fatty acids were higher in children with extremely severe clinical ADHD condition score, as compared to milder ADHD scores and to control children (0.72±0.18, 0.64±0.20, 0.61±0.22, 0.49±0.18, p=0.010, accordingly). Conclusion: Children with ADHD have higher levels of trans-fatty acids in RBCs, compared to children without ADHD. This study points to a possible link between trans-fatty acids and ADHD. Understanding these findings and the clinical meaning will potentially contribute to a more targeted dietary intervention.